Multi-scaler 3D modelling to reconstruct an experiential landscape: An example from a worker's cottage at Mount Dutton Bay, South Australia. (February 2019) - Kowlessar, Jarrad; Benjamin, Jonathan; Moffat, Ian; Van Duivenvoorde, Wendy
Abstract: New advances in 3D GIS provide the opportunity to create and interact with spatial datasets that are both empirical and experiential, thus bridging the historical divide between cartography and phenomenology. Survey and photogrammetry data from the colonial-era woolshed and port of Mount Dutton Bay in South Australia are used to create a visually realistic 3D landscape model. Viewshed analysis provided important information about the use of space and construction techniques for the shearers' cottage on this site. The results demonstrate that rigorous quantitative analysis is not incompatible with understanding the human experience of an archaeological site, and therefore open up exciting new avenues of archaeological enquiry. Highlights: Three dimensional data provides unique insights into archaeological landscapes. Archaeological interpretations can be developed from an intuitive human perspective. Statistical analysis can be used to test intuited hypothesis. A sparse colonial era coastal landscape demonstrates a 3D dimensional approach. Quantitative analysis is compatible with intuitive human interpretation.